2019
DOI: 10.1002/vms3.166
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the histopathological extent of neoplastic infiltration in intestinal tumours in cats

Abstract: With the exception of intestinal lymphoma, surgery is the most commonly recommended treatment for solitary feline intestinal tumours. However, there is a lack of evidence to substantiate resection margin recommendations for these tumours. The aim of this study was to add knowledge concerning resection margins for discrete intestinal masses in cats. Thirty confirmed feline intestinal tumours removed at veterinary centres across the UK from March 2017 to March 2018 underwent histological assessment at the palpab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
(36 reference statements)
1
4
0
Order By: Relevance
“…Improved diagnostics and therapeutic options, as well as an increasing willingness of patient owners to perform more advanced diagnostic measures, such as the immunohistochemical subtyping of lymphomas, may have contributed to the higher proportion of gastrointestinal lymphomas in the present pathologybased investigation. The low percentage of spindle cell tumours and mast cell tumours, along with the low incidence of neoplasms in cats younger than seven years of age, were consistent with the observations of other authors [7,[47][48][49]. However, we should be aware that data from pathological cases do not reflect the proportion of tumour diseases in cats in daily veterinary practice, since endoscopic or laparoscopic sampling is often only performed in the further course of the diagnosis of tumour diseases and only if advanced treatment is planned.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Improved diagnostics and therapeutic options, as well as an increasing willingness of patient owners to perform more advanced diagnostic measures, such as the immunohistochemical subtyping of lymphomas, may have contributed to the higher proportion of gastrointestinal lymphomas in the present pathologybased investigation. The low percentage of spindle cell tumours and mast cell tumours, along with the low incidence of neoplasms in cats younger than seven years of age, were consistent with the observations of other authors [7,[47][48][49]. However, we should be aware that data from pathological cases do not reflect the proportion of tumour diseases in cats in daily veterinary practice, since endoscopic or laparoscopic sampling is often only performed in the further course of the diagnosis of tumour diseases and only if advanced treatment is planned.…”
Section: Discussionsupporting
confidence: 91%
“…It has been shown that intestinal neoplasms in cats (except for lymphomas) should be resected with 4 cm margins in oral and aboral directions [49]. In our study, large intestinal carcinomas especially lacked free margins, probably due to the anatomical limitations of surgery.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Splenectomy is the standard therapy for cats with splenic mastocytosis and provides longer disease-free survival than chemotherapy alone (856 days vs. 342 days, respectively) (Evans et al, 2018). Cats with intestinal MCT historically carry a guarded prognosis and metastasis to mesenteric lymph nodes is common (Barrett et al, 2018;Morrice, Polton, & Beck, 2019;Sabattini et al, 2016). However, recent literature describes variable biologic behaviour of feline gastrointestinal MCT with the overall median survival time of 31 cats to be 531 days in one study (Barrett et al, 2018) and 35% of cats surviving more than 1-year post-diagnosis in a different study which included a case where no treatment or surgery was received (Sabattini et al, 2016).…”
Section: Treatment Of Feline Mctmentioning
confidence: 99%
“…Rates of local and distant metastases have been reported to range from 55 to 76 percent ( 3 7 ). Wide surgical resection with or without adjuvant chemotherapy is currently the primary mode of therapy ( 2 , 8 , 9 ). Existing retrospective studies reporting on prognostic factors and survival times describe relatively small populations of cats, but consistently suggest that outcomes are highly variable and that prolonged survival times are occasionally observed in the presence of systemic disease ( 4 , 6 , 7 , 10 ).…”
Section: Introductionmentioning
confidence: 99%